Makna Sains Dalam Surat An-Nahl : 65 Dalam Perspektif Tafsir Ilmi Dan Tantangan Ketahanan Pangan di Pandeglang Carita - Ilham Akbar, Muhammad; Muhammad Fakhrial Dewanda Zain; Hadi, Khaestya Hadi Wibawa; Akbar Zailani; Andi Rosa (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This research aims to discuss the meanings of science in Surah An-Nahl Verse 56 through the approach of scientific interpretation which with the letter can be related between the combination of Surah An-Nahl 56 to food security in the Pandeglang Carita area. The interpretation of science as a method rather than interpretation seeks a concept of how the Qur'an can adapt and can distribute its role to global and economic challenges as is the case in Pandeglang Carita. More than that, the interpretation of knowledge can be used as a source of role in studying and processing natural resources in this world. In the view of the Tafsir of science in Surah An-Nahl: 65 there is a correlation with the problems in Pandeglang Carita. The interpretation of knowledge in Surah An-Nahl can make the people of Pandeglang Carita improve the quality and general knowledge in managing resources in their area, especially in Pandeglang Carita in the sea area. Pandeglang Carita has many problems in knowing the benefits of marine resources and components. The Tafsir Ilmi can be a solution to the detention of food and staple food of the Pandeglang Carita community Keywords : Tafsir Ilmi, Surah An-Nahl 65, Pandeglang Carita, Food Security